Exploring the relationships between science and technology input and output indicators: A comparison between developed, fast developing World and Turkey - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2014)
From a scientometric perspective, this paper aims to discuss the relationships between the financial Science and Technology input indicators like R&D Expenditures and Payments for external technology transfer (royalties and License fees) to the Science and Technology output indicators like Patents/patent applications and receipts from technology transfer (Royalties and licence fees). Although the efficiency of R&D and economical returns of R&D spendings has always been questioned and searched by the scholars from developmental economics, scientometrics and technology and innovation management fields, the performance of developing countries for utilizing R&D investments is still worth searching. In this study, we explored the trends of and relationships between Science and Technology Input indicators like R&D expenditure, Payments (royalties and License fees) and Science and Technology output indicators like Patents/patent applications and receipts from technology transfer (Royalties and licence fees) for developed countries that are called as G-7 countries, fast developing countries that are called as BRIC (Brazil, Russian federation, India and China) and Turkey. Based on the data of World Bank, S&T input and output indicators are analyzed by calculating the spatial-index of each country for each indicator between the years of 1996-2010 where data of all countries are available. Indicators are tested for their correlations. The differences between G-8, BRIC countries and Turkey are also outlined. © 2014 PICMET.